Quantifying excavation response to accurately inform numerical modelling analysis at Oyu Tolgoi - Simanjuntak, K; Sharrock, G; Rwodzi, L; Ekkerd, J; Mgumbwa, J; Mardiansyah, F (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
The Panel 0 footprint at Oyu Tolgoi has been successfully established in a structurally complex rock mass of variable strength at a depth of 1,300 m. To monitor the rock mass response and the excavation stability, Panel 0 was well instrumented with multipoint borehole extensometers, convergence pins, borehole monitoring, convergence scanning and damage mapping. Thus, during undercutting to surface breakthrough, extensive data related to footprint stability performance were collected on extraction, undercut and apex levels. This data was analysed using conventional data analysis and numerical methods to delineate ground reactions and ground behaviour. Assessments indicated ground behaviour is influenced by several parameters including (a) geotechnical properties, (b) faults and defects, and (c) mining-induced stress. Mining-induced stress is influenced by local excavation geometry, cave volume, cave shape and distance from the cave. The objective of this paper is to share the framework developed to understand ground behaviour through analysis of the monitoring data and numerical modelling.
Keywords: Oyu Tolgoi; block cave; monitoring data; stability; caveability; convergence; numerical model; FLAC3D; bonded block modelling; calibration